Malignant Microbes: Using Environmental History to Connect the Fields of Plant and Human Epidemiology - Plishka, Matthew (Journal for the History of Environment and Society, 2020)
Abstract This article examines the commonalities between plant and human pandemics to show how studying the two together can help us better understand how pathogens operate. It demonstrates how many of the contributing factors to the spread of COVID-19, including mobility, migration, labour regimes, and engineered and natural infrastructures, are also factors in the spread of plant pandemics. It utilises the framework of multispecies studies to analyse microbes and their movement and incorporates political ecology to highlight how officials’ response, or lack thereof, to the movement of microbes, is critical to how quickly pathogens spread. To show how studying plant pandemics can help us understand human ones, this article presents the case study of the twentieth century Jamaican banana industry’s battle against Panama Disease, a fungus that eventually wiped out all of the original commercial banana variety. The lessons of the fight against Panama Disease, such as the need to focus on the carrier state, the importance of tracing the movement of microbes, and the dangers of overconfidence in combating disease, are all applicable to the current race to mitigate the spread of COVID-19.